Adalimumab versus adalimumab and methotrexate for the treatment of juvenile idiopathic arthritis: long-term data from the German BIKER registry. (4th March 2019) - Klein, A; Becker, I; Minden, K; Foeldvari, I; Haas, JP; Horneff, G
Abstract : Objective : Adalimumab (ADA) has become a valuable treatment option for juvenile idiopathic arthritis (JIA). The importance of combination with methotrexate (MTX) is unclear. Method : Data from the German Biologics in Paediatric Rheumatology (BIKER) registry are reported. Response to treatment was analysed using JIA American College of Rheumatology (ACR) scores, 10-joint Juvenile Arthritis Disease Activity Score (JADAS10), and improvement of functional status and ACR inactive disease criteria. Compa-risons between rates of adverse events (AEs) and serious adverse events (SAEs) provided data for the safety assessment. Results : Overall, 584 patients with non-systemic JIA started ADA therapy, 61% of whom received concomitant MTX treatment at baseline. The latter patients were younger (p < 0.001), with shorter disease duration (p = 0.001), more frequently had antinuclear antibodies (p = 0.04), and had higher baseline JADAS10 scores (p = 0.03). In patients with ADA monotherapy, enthesitis-related arthritis (p = 0.004) and presence of human leucocyte antigen-B27 (p = 0.008) were documented more often. Mean treatment duration in both cohorts was 15 months. Comparable last follow-up rates for JIA ACR 30/50/70/90% response, JADAS minimal disease activity, JADAS remission, and ACR inactive disease were, respectively, 75/72/64/49%, 66%, 46%, and 58% for ADA monotherapy, and 77/72/61/45%, 64%, 48%, and 55%, for ADA + MTX. During 1082 patient-years (PY) of ADA exposure, 725 AEs (67/100 PY), including 57 SAEs (5.3/100 PY), were reported. Serious infections were reported in 10 patients (0.9/100 PY) and 11 (1.0/100 PY) had varicella infections/zoster reactivation. Rates of AEs, SAEs, infectious events, and serious infections did not differ between the cohorts. Elevated transaminases (p = 0.005) and gastrointestinal events (p < 0.0001) were reported more often in the combination cohort. Two pregnancies and no deaths were reported. Conclusion : ADA demonstrated an acceptable risk profile and high percentages of patients in both cohorts showed sufficient treatment response. No differences in treatment response or adherence to treatment were found.